PERANCANGAN KAMPANYE SOSIAL PEMANFAATAN LIMBAH KULIT JAGUNG SEBAGAI PRODUK KERAJINAN - Nurul Atifah Syafitri; Husni Mubarat; Bobby Halim (VisArt: Jurnal Seni Rupa dan Design, 2023)
Abstract: Corn is a well-known staple food in Indonesia, and its high consumption results in a lot of natural waste, such as corn husks and corn cobs. According to the Infopublic.id website, South Sumatra is listed as the fifth largest corn producer in Indonesia, with a corn farming area of 112,000 hectares and a total corn production of 707,546 tons. Based on the results of the questionnaire, it can be concluded that the people of Palembang do not know that corn plant waste can be reused other than being used as animal feed. In the process of overcoming these problems, the author uses the design thinking method through the 5W+1H method (what, why, who, where, why, how) for data collection and data analysis so as to produce a model that can be applied to actual scenario ideas. The main media used is a tutorial book on the utilization of corn husk waste, which includes information on the utilization of corn husk waste and tutorials on processing corn husk waste, news media such as posters, peeling of husks, and supporting media such as t-shirts, glasses, stickers, mini notebooks, hanging clothing, handicraft supply containers, decorative flowers, decorative lights, and mascots, which.